A Conditioning-Strengthened Circuit From CA1 of Dorsal Hippocampus to Basolateral Amygdala Participates in Morphine-Withdrawal Memory Retrieval - Ma, Qianqian; Fu, Yali; Cao, Zixuan; Shao, Da; Song, Jiaojiao; Sheng, Huan; Yang, Li; Cui, Dongyang; Chen, Ming; Zhao, Fei; Luo, Min-Hua; Lai, Bin; et al. (Frontiers in Neuroscience, 2020)
Conditioned context-induced retrieval of drug-withdrawal memory contributes to drug relapse. The basolateral amygdala (BLA) is an important brain region that is involved in conditioned context-induced retrieval of morphine-withdrawal memory. However, the upstream pathways of the activation of the BLA by conditioned context remains to be studied. The present results show that the CA1 of dorsal hippocampus is an upstream brain region of the activation of the BLA during conditioned context-induced morphine-withdrawal memory retrieval; the indirect connection from the CA1 of dorsal hippocampus to the BLA is enhanced in mice with conditioned place aversion; the postrhinal cortex (POR) is a brain region that connects the CA1 of dorsal hippocampus and the activation of the BLA during conditioned context-induced retrieval of morphine-withdrawal memory. These results suggest that a conditioning-strengthened indirect circuit from the CA1 of dorsal hippocampus to the BLA through the POR participates in morphine-withdrawal memory retrieval.